On the Structural, Optical and Electrical Characterization of Zinc Oxide and Aluminium doped Zinc Oxide for Optoelectronic Applications - Oluwaseun, Adedokun; Adetunji, Akinlade Johson; Ibironke, Busari Debora; Lydia, Adedeji Olufunke; Bello, Ismalia Taiwo (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Zinc Oxide (ZnO) and Aluminium doped Zinc Oxide (AZO) thin films are deposited on the glass slides by sol-gel spin coating technique. Zinc acetate dehydrate, 2 methoxyethanol, and diethanolamine are respectively used as a precursor, solvent, and stabilizer. Aluminium nitrate nonahydrate was used as the dopant source to obtain the atomic percentage of the dopant of 2%, 4%, 6% and 8%. The structural, optical, and electrical properties of the films were investigated using X-ray Diffraction (XRD), UV-visible spectrophotometry, and a Four-point probe technique respectively. The results from structural analyses show that the films are polycrystalline with a hexagonal wurtzite structure and a preferential orientation alongside the \(c\)-axis. The value obtained for the unit cell \(a=3.020\) A and \(c= 5.108\) A are in line with the reported literature. The transmittance of the films was observed within the visible region of the spectrum and the optical bandgap of the un-doped ZnO was established to be around 4.11 eV. However, the optical bandgap of the AZO films (4 and 6 at %) marginally decreases with doping concentration, which may be ascribed to the shrinkage of band effect due to the increase in carrier concentration. The lowest resistivity of \(3.53× 10^-3 Ω\) cm was observed for the doping concentration of 2% of Al. From the results, it was established that as the doping concentration increases, the thicknesses of the thin films were increased. Likewise, the increase in doping leads to a better uniformly distributed absorption spectra of the deposited AZO thin films.